Evaluation of circ_100219 and miR-135b in serum and exosomes of healthy pregnant women. (17th November 2021) - Montagnana, Martina; Benati, Marco; Tagetti, Angela; Raffaelli, Ricciarda; Danese, Elisa; Zatti, Nicoletta; Marcon, Denise; Branz, Lorella; Micheli, Chiara; Franchi, Massimo; Fava, Cristiano; Lippi, Giuseppe
Abstract: Aim: Circular RNAs (circRNAs) are recently discovered and highly stable noncoding RNAs acting as gene regulators. These circRNAs can function as miRNA sponges, thereby upregulating or downregulating miRNA target gene expression. MiR-135b is expressed in placenta tissue and can be found in maternal circulation, thus playing a functional role in pregnancy. This miR is a target of circ_100219. This preliminary study was aimed to evaluate circ_100219 and miR-135b expression in pregnant and nonpregnant women, and explore the relationship between circ_100219 and miR-135b in serum and exosomes. Methods: Total RNA was isolated from serum and exosomes of 30 healthy pregnant women (32.9 ± 5.1 years) between 23–27 gestational weeks and 30 healthy nonpregnant women (31.3 ± 5.4 years). Quantitative real-time polymerase chain reaction (qRT-PCR) was used to quantify circ_100219 and miR-135b expression. GAPDH and U6 snRNA were chosen as reference for normalizing expression levels. The differences between pregnant and nonpregnant women were assessed with Mann–Whitney test and correlation with Spearman's test. Results: The circ_100219 expression levels were significantly lower both in serum and exosomes of second trimester pregnant women compared to the control group ( p  < .0001), whilst Mir-135b expression levels were significantly higher in pregnant than in the control group ( p  < .0001). A significant negative correlation was observed between circ_100219 and miR-135b expression levels in both serum and exosomes ( r  = −0.34 and p  = .009; r  = −0.31 and p  = .01, respectively). The circ_100219:miR-135b ratio was significantly increased in nonpregnant women compared to the pregnant group, in both serum and exosomes (49.0 versus 1.1, p  < .0001 and 2042.4 versus 28.5, p  < .0001, respectively). Conclusions: Our results confirm a role for circ_100219 and miR-135b in physiological pregnancy. Further studies are needed to investigate the circ_100219:miR-135b ratio in pregnancy complications.